Apparent diffusion coefficient in the analysis of prostate cancer: determination of optimal b-value pair to differentiate normal from malignant tissue - Adubeiro, Nuno (2019)
Purpose Determining optimal b-value pair for differentiation between normal and prostate cancer (PCa) tissues. Methods Forty-three patients with diagnosis or PCa symptoms were included. Apparent diffusion coefficient (ADC) was estimated using minimum and maximum b-values of 0, 50, 100, 150, 200, 500 s/mm2 and 500, 800, 1100, 1400, 1700 and 2000s/mm2, respectively. Diagnostic performances were evaluated when Area-under-the-curve (AUC) > 95%. Results 15 of the 35 b-values pair surpassed this AUC threshold. The pair (50, 2000 s/mm2) provided the highest AUC (96%) with ADC cutoff 0.89 × 10–3 mm2/s, sensitivity 95.5%, specificity 93.2% and accuracy 94.4%. Conclusions The best b-value pair was b = 50, 2000 s/mm2.